(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the effects of pictures, story telling and coloring books in reducing anxiety in pediatric patients preoperatively as compared to pharmacologic interventions. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at the Department of Anaesthesia Nishtar Hospital, Bakhtawar Amin Medical and Dental College Multan and Shahida Islam Medical College, Lodhran from February 2017 to February 2018. Materials and Methods: Study was conducted upon 240 children. Patients were allocated in two groups (pharmacologic intervention versus distraction techniques). The preoperative anxiety of children was determined by using Modified Yale Preoperative Anxiety Scale (mYPAS) score. Vital signs of the patients were recorded before anesthesia and during the recovery period. Other variables include age,State–Trait Anxiety Inventory for Children(STAIC) score, Cystoscopy, EUA eyes, Excision of cyst and hernia. Results: The mean mYPAS total score of the intervention group (play distraction) and control (preoperative medication) patients were 10.74±1.18 and 10.55±0.91 respectively. The mean difference was 0.186. The difference was statistically insignificant (p=0.172). The mean STAIC total score of the intervention group (play distraction) and control (preoperative medication) patients were 20.88±2.24 and 20.85±2.07 respectively. The mean difference was 0.037. The difference was statistically insignificant (p=0.894). Conclusion: Distraction technique is as effective as substitute to the conventional pharmacological therapies in reducing preoperative anxiety among pediatric patients. It is safe and easily applicable technique with remarkable post operative outcome.